(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Appearance of resistance to available antibacterial and anticancer drugs became a major challenge in the recent time. Hence, finding of new antibacterial and anticancer compounds become highly essential. Pyrazolines and benzimidazoles were reported to have potent antibacterial and anticancer activity. Therefore,a hybrid tactic has been used, combining the core structure of tentatively active benzimidazole and pyrazoline moiety in to a single molecule. Targeted compounds were obtained by the cyclizing N-substituted benzimidazole chalcones with hydrazine hydrate. The structure of compounds were characterized by taking the help of spectroscopic techniques like IR, 1H, 13C-NMR and mass. Compounds were evaluated for their growth inhibitory potential against human breast cancer cell line MDA-MB-231. Furthermore, they were also evaluated against gram positive and negative bacteria. Compounds 4a (GI50 = 26.13μM) and 4c (GI50=12.27μM) found to possess significant anticancer activity. Similarly, Compound 5a was significantly active against Staphylococcus aureus at a concentration of 62.5 µg mL-1.